1967
DOI: 10.1104/pp.42.12.1787
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Indoleacetic Acid from Tryptophan-14C in Cell-free Extracts of Pea Shoot Tips

Abstract: Summary. A 2-step, 1-d:,mens-ional thn-layer chromatograph-c proceduire fnr isolating indoleacetic ac:d (IAA) was developed and util:zed in inve,t at:ons of the biosynthesis of JAA from tryl)to,)han-_4C in cell-fre'-extracts of ipea (Pi.sun sativitmn L.) shoot tips. Identfcat;on of a 14C-prodnict as IAA was bv (a) co-chromatograT)hv of atitheiiitc IAA and '4C-pro(duict on th.:n-layer chromatography, and (b) gas-liqu-;d and thin-laver chromategraphy of authentic and presumptive IAA methyl esters. Dalysis of enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1968
1968
1989
1989

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Hayashi and Murakami (1953) first demonstrated that GA increases elongation growth of pea stem segments incubated in L-Trp. The finding that both tryptamine and IPyA induced elongation is in agreement with reports that both can act as precursors in pea, though the TAT pathway seems to be the only significant source of IAA in Pisum in vivo; Moore andShaner (1967, 1968) demonstrated that while both Trp and tryptamine were converted to IAA, Trp was not converted to tryptamine, implying that TDC is not an IAA biosynthetic enzyme, and another report showed that Trp decarboxylation is not specifically related to IAA synthesis (Reed 1968). Taken together, all of these results suggest that the conversion of L-Trp to IPyA is the rate-limiting step in IAA biosynthesis in this system.…”
Section: Growth Of Pea Stem Segmentssupporting
confidence: 92%
See 1 more Smart Citation
“…Hayashi and Murakami (1953) first demonstrated that GA increases elongation growth of pea stem segments incubated in L-Trp. The finding that both tryptamine and IPyA induced elongation is in agreement with reports that both can act as precursors in pea, though the TAT pathway seems to be the only significant source of IAA in Pisum in vivo; Moore andShaner (1967, 1968) demonstrated that while both Trp and tryptamine were converted to IAA, Trp was not converted to tryptamine, implying that TDC is not an IAA biosynthetic enzyme, and another report showed that Trp decarboxylation is not specifically related to IAA synthesis (Reed 1968). Taken together, all of these results suggest that the conversion of L-Trp to IPyA is the rate-limiting step in IAA biosynthesis in this system.…”
Section: Growth Of Pea Stem Segmentssupporting
confidence: 92%
“…There are a number of reports in which D-Trp was at least as effective as L-Trp as an auxin precursor (discussed in Miura and Mills 1971). Many studies of the role of Trp as an IAA precursor used racemic mixtures of D-and L-Trp in feeding experiments or compared metabolism of labeled D-and L-Trp, in which levels of isomeric contamination exceeded the amounts of IAA formed (e.g., Kim and Rohringer 1969, Moore and Shaner 1967, 1968, Wightman and Cohen 1968. It now seems clear that care must be taken to ascertain isomeric purity and that the assumption that the D isomer is inert is not well founded.…”
Section: Ti-yptophan Stereoisomers and Iaa Biosynthesismentioning
confidence: 99%
“…Particular attention was given to the formation of indolepyruvate from tryptophan via transamination because of the implication of that reaction in the biosynthesis of IAA in peas (20)(21)(22). The formation of equimolar yields of indolepyruvate and glutamate from tryptophan and a-ketoglutarate was readily demonstrable under anaerobic conditions, which prevented loss of indolepyruvate.…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of these investigations was to purify partially and ascertain some properties of a transaminase fraction from pea shoots and to attempt to corroborate the evidence reported by Moore (20) and Moore and Shaner (21,22) Preparation of Enzyme Extract. Each sample of shoot tips was homogenized in a chilled mortar and pestle with 2 ml of 0.5 M borate buffer (pH 8.5), containing 150 ltM chloramphenicol and 1 mm dithiothreitol, per g fresh weight of tissue.…”
mentioning
confidence: 98%
“…The possibility that bacterial contamination could account for the auxin synthesis ascribed to plant tissues in recent reports (7,13) was dismissed for a number of reasons including the following: surface sterilization procedures were employed and were followed by a thorough washing of the tissue; high speed centrifugation techniques were used; a short time interval was used for the enzyme assays; and antibiotics were included in the reaction mixtures. (5).…”
mentioning
confidence: 99%